Potential of Technology Application on Building Facilities Management: Schedule of Maintenance - Hasanuddin, Nur’ Adibah Izmahani; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2024)
Building Facility Management refers to the routine and extraordinary operations required to ensure that a physical environment meets the needs and functions for which it was designed and built throughout its life cycle. As mentioned from Facility Management Green Key FM, poor facility management results in excessive demands for unplanned periodic maintenance expenses.  The objective of this research is to identify the challenges of proper schedule maintenance in buildings, to identify the risks that would occur of improper schedule maintenance in building and to propose the potential of technology application on prepare schedule maintenance in building. The method that has been used in this study is quantitative method that is by collecting information through  questionnaires survey form through the form of email and other applications to gather data in order to archive the research objectives.  A total of 132 questionnaires were distributed and only 103 respondents received the questionnaire. The study identified "Unclear job descriptions" and "Reduced comfort and safety" for the challenges of proper schedule maintenance in buildings and the risks that would occur of improper schedule maintenance in building as the key obstacles, but it also highlighted the potential of technology application on prepare schedule maintenance in building on how mobile applications may improve building upkeep. Overall, by identifying maintenance difficulties, related hazards, and technology's role in enhancing building facilities management, the study successfully met its objectives. In conclusion, good schedule maintenance practices in building facility management can reduce risks, unscheduled maintenance costs, and building performance.